2017
DOI: 10.3389/fphys.2017.00676
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Timing of Swallow in the Respiratory Cycle Causes Breathing–Swallowing Discoordination

Abstract: Rationale: Swallowing during inspiration and swallowing immediately followed by inspiration increase the chances of aspiration and may cause disease exacerbation. However, the mechanisms by which such breathing–swallowing discoordination occurs are not well-understood.Objectives: We hypothesized that breathing–swallowing discoordination occurs when the timing of the swallow in the respiratory cycle is inappropriate. To test this hypothesis, we monitored respiration and swallowing activity in healthy subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 41 publications
(51 reference statements)
1
58
2
Order By: Relevance
“…However, a possible function could be the proper temporal coordination of breathing with swallowing movements (Hardemark Cedborg et al, 2009). Inappropriate temporal coordination of swallowing with respiration can lead to dysphagia, increasing the risk of aspiration pneumonia (Yagi et al, 2017). Dysphagia is a common symptom in patients with cerebellar disease (Ramio-Torrentia et al, 2006) and a potential anatomical substrate for a cerebellar coordination of brain stem pattern generators controlling breathing and other orofacial movements exists in form of extensive reciprocal connections between the cerebellum and brain stem (Asanuma et al, 1983;Teune et al, 2000;Whiteside and Snider, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…However, a possible function could be the proper temporal coordination of breathing with swallowing movements (Hardemark Cedborg et al, 2009). Inappropriate temporal coordination of swallowing with respiration can lead to dysphagia, increasing the risk of aspiration pneumonia (Yagi et al, 2017). Dysphagia is a common symptom in patients with cerebellar disease (Ramio-Torrentia et al, 2006) and a potential anatomical substrate for a cerebellar coordination of brain stem pattern generators controlling breathing and other orofacial movements exists in form of extensive reciprocal connections between the cerebellum and brain stem (Asanuma et al, 1983;Teune et al, 2000;Whiteside and Snider, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies have shown that swallows occur preferentially at phase-transitions of the respiratory and ventilatory cycle, i.e., inspiration to early-expiration (I-early Exp), early-expiration to late-expiration (early Exp-late Exp), and late-expiration to inspiration (late Exp-I) ( Dick et al, 1993 ; Paydarfar and Buerkel, 1995 ; Ono et al, 1998 ). Swallows have also been reported to occur during inspiration, i.e., I-I or I-swallow, as well as to interrupt the inspiratory phase of breathing (interrupted-I swallow) ( Feroah et al, 2002 ; Roberge et al, 2007 ; Wheeler Hegland et al, 2009 ; Bonis et al, 2011 ; Wheeler Hegland et al, 2011 ; Yagi et al, 2017 ). Overall, five types of swallow patterns have been proposed, including I-swallow, interrupted-I, I-Exp, early Exp-late Exp, and Exp-I, despite most single swallows occurring predominantly during the I-Exp and early Exp-late Exp phase-transitions ( Martin-Harris et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study we show swallow related apnea duration has no change when comparing between the swallow stimuli and combined stimuli trials. We have found in our study the apnea duration during swallow to be 1.1s and 1.2s for swallow stimuli and combined stimuli trials, respectively, and within the range of previous reports (Clark, 1920;Hiss, Treole, & Stuart, 2001;Kijima, Isono, & Nishino, 1999;Martin, Logemann, Shaker, & Dodds, 1994b;Nishino, Yonezawa, & Honda, 1985;Yagi, Oku, Nagami, Yamagata, Kayashita, Ishikawa, Domen, & Takahashi, 2017).…”
Section: Apnea Durationsupporting
confidence: 92%
“…Swallow related apnea has been studied across many different populations, genders, ages and conditions all in healthy adult humans, but this is the first study, to our knowledge, to study apnea duration in coordination with cough. Studies report swallow related apnea durations ranging from 0.93-1.5s (Clark, 1920;Hiss, Treole, & Stuart, 2001; Kijima, Isono, & Nishino, 1999;Martin, Logemann, Shaker, & Dodds, 1994b;Nishino, Yonezawa, & Honda, 1985;Yagi, Oku, Nagami, Yamagata, Kayashita, Ishikawa, Domen, & Takahashi, 2017) in healthy adult human subjects. Swallow apnea duration was determined at normocapnic and hypercapnic conditions 1.3 and 0.8 s, respectively by Hardemark et al (2009).…”
Section: Apnea Durationmentioning
confidence: 99%